INFLUENCE OF THE ENDOTHELIAL NITRIC OXIDE SYNTHASE POLYMORPHISM ON THE PROGRESSION OF AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE AND IgA NEPHROPATHY - Merta, Miroslav; Reiterová, Jana; Tesa, Vladimír; Štekrová, Jitka; Viklický, Ond ej (Renal failure, 2002)
Background: The reason of variability of clinical course and progression to end-stage renal failure (ESRF) of two widespread chronic nephropathies--autosomal dominant polycystic kidney disease (ADPKD) and IgA nephropathy (IGAN) is not clear. The endothelial dysfunction is considered in the number of factors possibly influencing the prognosis of these nephropathies. Our study tried to verify the hypothesis that endothelial nitric oxide synthase (ecNOS) gene polymorphisms in intron 4 could have some relevance to the progression of ADPKD and or IgA nephropathy. Methods: We examined 128 Czech patients with ADPKD (62 males, 66 females) and 93 patients with IGAN (51 males, 42 females). As a control group we used 100 genetically unrelated healthy subjects (50 men, 50 women, mean age 51.2 ± 8.2). The genomic DNA was amplified by polymerase chain reaction (PCR) and the products were separated on 1.5% agarose gel and visualized by ultraviolet transillumination. We compared homozygous subjects for ecNOSb allele with homozygous and heterozygous subjects for ecNOSa allele. Results: The frequencies of ecNOSa b + a a and ecNOSb b genotypes were 19% (19 100) and 81% (81 100) in the control group. The frequencies of ecNOSa b + a a and ecNOSb b genotypes in ADPKD patients were: 26.6% (8 30) and 73.4% (22 30) in ADPKD patients with normal renal function, 30% (9 30) and 70% (21 30) in ADPKD with ESRF, 35.2% (18 51) and 64.8% (33 51) in young ADPKD patients, 60% (12 20) and 40% (8 20) in ADPKD patients with ESRF later than in 62 years. In IGAN the frequencies of ecNOSa b + a a and ecNOSb b genotypes were 24% (12 50) and 76% (38 50) in IgA with normal renal function and 20.9 % (9 43) and 79.1% (38 43) in IgA with ESRF. Conclusion: Both in ADPKD and IGAN groups there was no significant difference in the frequencies of ecNOS genotypes between patients with normal renal function and age matched patients with ESRF and between patients with normal renal function and control group. The frequency of ecNOS a allele was significantly higher in a number limited group ADPKD patients with ESRF later than in 62 years (Chi-square test p < 0.05). This higher frequency of a allele among ADPKD patients with later onset of ESRF could suggest the trend of positive influence of a allele in ADPKD patients.